Developmental potential of surplus morulas with delayed and/or incomplete compaction after freezing-thawing procedures - Ni-Chin Tsai; Yu-Ting Su; Yu-Ju Lin; Hsin-Ju Chiang; Fu-Jen Huang; Fu-Tsai Kung; Kuo-Chung Lan (BMC, 2019)
Abstract Background Morulas with delayed growth sometimes coexist with blastocysts. There is still limited evidence regarding the optimal disposal of surplus morulas. With the advancement of vitrification, the freezing-thawing technique has been widely applied to zygotes with 2 pronuclei, as well as embryos at the cleavage and blastocyst stages. The freezing of morulas, however, has rarely been discussed. The purpose of this study was to investigate whether these poor-quality and slow-growing morulas are worthy of cryopreservation. Methods This is a retrospective, observational, proof-of-concept study. A total of 1033 day 5/6 surplus morulas were cryopreserved from January 2015 to December 2018. The study included 167 women undergoing 180 frozen embryo transfer cycles. After the morulas underwent freezing-thawing procedures, their development was monitored for an additional day. The primary outcome was the blastocyst formation rate. Secondary outcomes were clinical pregnancy rate, live birth rate and abortion rate. Results A total of 347 surplus morulas were thawed. All studied morulas showed delayed compaction (day 5, n = 329; day 6, n = 18) and were graded as having low (M1, n = 54), medium (M2, n = 138) or high (M3, n = 155) fragmentation. The post-thaw survival rate was 79.3%. After 1 day in extended culture, the blastocyst formation rate was 66.6%, and the top-quality blastocyst formation rate was 23.6%. The day 5 morulas graded as M1, M2, and M3 had blastocyst formation rates of 88.9, 74.0, and 52.8% (p < 0.001), respectively, and the top-quality blastocyst formation rates were 64.8, 25.2, and 9.0% (p < 0.001), respectively. The clinical pregnancy rate was 33.6%. Conclusions The post-thaw blastocyst formation rate was satisfactory, with approximately one-half of heavily fragmented morulas (M3) developing into blastocysts. Most of the poor-quality morulas were worth to freeze, with the reasonable goal of obtaining pregnancy and live birth. This alternative strategy may be a feasible approach for coping with poor-quality surplus morulas in non-PGS (preimplantation genetic screening) cycles.